2015
DOI: 10.1371/journal.pone.0136918
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Patients with Resected Oral Cavity Cancer and Simultaneous Second Primary Malignancies

Abstract: ObjectivesSimultaneous second primary tumors (SSPT) are not uncommon in patients with oral cavity squamous cell carcinoma (OSCC) living in areas where the habit of betel quid chewing is widespread. We sought to identify the main prognostic factors in OSCC patients with SSPT and incorporate them into a risk stratification scheme.MethodsA total of 1822 consecutive patients with primary OSCC treated between January 1996 and February 2014 were analyzed for the presence of SSPT. The 18-month and 5-year overall surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…SPMs have a significantly negative impact on the prognosis of HNSCC [37-39]. Overall survival (OS) in oral cancer patients with simultaneous SPM was significant lower than in those without simultaneous SPM (53% vs. 69%, 5-year OS) [38,39]. OS with head and neck SPMs was better than that with non-head and neck SPMs in patients with tongue or laryngeal cancer (39% vs. 29%, 5-year OS) [40].…”
Section: Guidelines For Surgical Treatment Of Oral Cancermentioning
confidence: 99%
“…SPMs have a significantly negative impact on the prognosis of HNSCC [37-39]. Overall survival (OS) in oral cancer patients with simultaneous SPM was significant lower than in those without simultaneous SPM (53% vs. 69%, 5-year OS) [38,39]. OS with head and neck SPMs was better than that with non-head and neck SPMs in patients with tongue or laryngeal cancer (39% vs. 29%, 5-year OS) [40].…”
Section: Guidelines For Surgical Treatment Of Oral Cancermentioning
confidence: 99%
“…Previous studies mainly focused on the risk of developing an SPM after a known malignancy. Liao et al [ 9 ] discussed the main prognostic factors for oral cavity cancer patients with simultaneous SPM, and then developed a risk-stratification. Vassilev et al [ 10 ] provided a historical risk estimation of developing an SPM in patients with metastatic castration-resistant prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Despite advances in therapy, the 5‐year survival for patients with OC is still unfavorable (Liao et al., 2015). A Taiwanese study showed that the 5‐year survival for OSCC patients was 68% and for patients with simultaneous second primary tumors was 53% (Liao et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Despite advances in therapy, the 5‐year survival for patients with OC is still unfavorable (Liao et al., 2015). A Taiwanese study showed that the 5‐year survival for OSCC patients was 68% and for patients with simultaneous second primary tumors was 53% (Liao et al., 2015). To date, primary surgical resection with or without postoperative radiation or chemoradiation remains as the standard of care for OC (Montero & Patel, 2015).…”
Section: Introductionmentioning
confidence: 99%